GIS development and application for planning and monitoring of urban growth in Klang Valley Region, West Malaysia - Yaakup, Ahris; Said, Mohamad Nor; Shamsudin, Kamalruddin; Musa, Nuha (1999)

(untitled)
Among the myriad of urbanization issues faced by the local authorities in the Klang Valley region includes traffic congestion, provision of housing and amenities and declining environmental situation. Within a rational planning approach, the quality of planning and decision making process can be substantially improved with valid data appropriately and efficiently handled. Against this background, this paper demonstrates the design and development of a GIS database as well as the customised applications for planning and monitoring the development of the region.